Some features of geological structure of the Shikotan Island (Lesser Kuril Arc)—A view from 'Space' - Evgeny P Terekhov; Anatoly V Mozherovsky (AIMS Geosciences)
In this paper, for the first time, we used Google Earth, an easily accessible method for obtaining geological information to study Shikotan Island (Lesser Kuril Arc). Google Earth flight mode made it possible to examine coastal cliffs on the island, which are inaccessible for hiking or walking, whereas 3-D visualization mode helped us study topographic features, tectonic dislocations, and sediment layering hidden by vegetation and soil, thereby significantly expanding understanding of the geologic structure of the island. Researchers conducting studies in the northwestern part of the island (Tat'yana Cape) discovered a previously unknown structure—a dike field. In the southern part, two thrust faults were identified: An unnamed peak and Tomari Mountain, previously considered a volcano. In the southwestern part of Shikotan Island, there are four unknown volcanic peaks. Together with the Notoro Volcano, they mark the rim of an interpreted caldera of a paleovolcano, which could have been the main unknown source of tuffaceous material for the Mesozoic-Cenozoic deposits of the Matakotanskaya, Malokuril'skaya, and Zelenovskaya Suites. It has been shown that the gabbroid massif of Tsunami Bay (northeastern part of the island) is an autochthonous (local) formation, and not allochthonous, that is, brought from the Pacific Ocean, as evidenced by an intrusive contact with the rocks of the Malokuril'skaya Suite. Despite these positive results, analysis of satellite images of Shikotan Island unexpectedly has not confirmed the existence of the Central Shikotan thrust fault, the largest previously mapped tectonic structure on the island. This work confirms that Google Earth is a very useful tool for geological research in remote areas.